2014
DOI: 10.1902/jop.2014.140244
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress Stimulates Osteogenic Differentiation of Human Periodontal Ligament Cells via the Extracellular Signal‐Regulated Kinase 1/2 and p38 Mitogen‐Activated Protein Kinase Signaling Pathways

Abstract: FSS is an effective approach for stimulating osteogenic differentiation of hPDLCs. The ERK1/2 and p38 MAPK signaling pathways are involved in this cellular process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…In this study, upregulation of osteogenic gene expression was observed in cells under continuous tensile strain (Li et al, 2014; Ren et al, 2015; Shen et al, 2014; Tang et al, 2014; Wei et al, 2008; Zhang et al, 2015). Animal experiments have demonstrated that continuous tensile strain generated by orthodontic appliances also upregulates osteogenic markers in PDL during orthodontic tooth movement (Kawarizadeh et al, 2005; Kim et al, 2012; Watanabe et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, upregulation of osteogenic gene expression was observed in cells under continuous tensile strain (Li et al, 2014; Ren et al, 2015; Shen et al, 2014; Tang et al, 2014; Wei et al, 2008; Zhang et al, 2015). Animal experiments have demonstrated that continuous tensile strain generated by orthodontic appliances also upregulates osteogenic markers in PDL during orthodontic tooth movement (Kawarizadeh et al, 2005; Kim et al, 2012; Watanabe et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…Numerous studies have shown that mechanical strain induces osteogenic differentiation of PDL cells by increasing osteogenic genes such as RUNX2 and OPN (Li et al, 2014; Ren et al, 2015; Tang et al, 2014; Zhang et al, 2015). Therefore, we investigated the effects of continuous tensile strain from the device on the osteogenic gene expression in HPL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical stimulation, such as shear, tensile, centrifugation, and vibration, has been shown to regulate osteogenic differentiation [28][29][30][31][32] . Cyclic tensile strain significantly enhanced RUNX2 and OSX expression in human periodontal ligament stem cells (hPDLSCs) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This observation correlated with the increase in Bmp2 , Bmp4 and Axin2 gene expression. BM-MSCs, periodontal ligament cells and dental pulp cells exposed to calcium-derived biomaterials have been reported to induce the upregulation of Bmp2 mRNA expression [8,39,40]. These studies implicated MAPK activity and AP-1 transcription factors in such effects [8,41].…”
Section: Discussionmentioning
confidence: 99%